Odpowiedzi

2010-02-17T23:27:29+01:00
0,5x-2,1y=5,7
x-1,4y=5,8

x-4,2y=11,4
x-1,4y=5,8

-2,8y=5,6
y=-2
x=3
2010-02-17T23:27:45+01:00
0,5x-2,1y=5,7
x-1,4y=5,8

x=5,8+1,4y
0,5(5,8+1,4y)-2,1y=5,7
2,9+0,7y-2,1y=5,7
-1,4y=5,7-2,9
y=2,8:-1,4
y=-2

x=5,8+1,4×(-2)
x=5,8-2,8
x=3

odp. x=3
y=-2
Najlepsza Odpowiedź!
2010-02-17T23:36:07+01:00
0,5x-2,1y=5,7
x-1,4y=5,8 /+1,4y

0,5x-2,1y=5,7
x = 5,8 + 1,4y

o,5(5,8+1,4y) - 2,1y = 5,7
x = 5,8 + 1,4y

2,9+0,7y-2,1y=5,7
x = 5,8 + 1,4y
-1,4y= 2,8 /:(-1,4)
x = 5,8 + 1,4y

y= -2
x=5,8+1,4*-2

y= -2
x= 3

Chyba dobrze ^^